Avifauna del bosque de pantano de palmeras del complejo turístico de Quistococha, Loreto – Perú - Rondona Bernuy, Jesús (2024)
The ornitofauna around the Iquitos city are threat by the urban growth and habitat destruction, being important to kwnon the species that live inside. From October to December 2021 and January 2022, the diversity and abundance of ornithofauna was evaluated in a palm swamp forest in the Quistococha Tourist Complex, Iquitos, Peru, through linear transect and auditory recognition. The results indicated a record of 72 species stood out. The relative abundance was heterogenous and in the common category 7 species were recorded, in quite common there were 11 species, in uncommon it was 8, in rare 45 species were recorded and in wandering 1 species (Tyrannus savana). It is concluded that the richness and species composition of the ornithofauna of the palm swamp forest of the Quistococha Tourist Complex was made up of 72 species.